Gender Toxicity in Language Communication - Bambang Nur Alamsyah Lubis; Irma Khoirot Daulay; Azizah Husda (Randwick International of Education and Linguistics Science Journal, 2021)
This study deals with gender toxicity in language communication. The aim of this study is to describe toxic language that is accepted by male and female in circle communication. Descriptive qualitative is used as research method of this study. This study described the result of society language communication recorder. The result, there are two kinds of toxic language, toxic muscularity and toxic femininity language that was accepted by male and female in language communication.